Entrepreneurship Development in the Balkans Perspective from Diverse Contexts - Ramadani, Veland (Emerald Publishing Limited, 2023)
Entrepreneurship Development in the Balkansdirectly engages questions of innovation and risk management within various types of entrepreneurship, including female, social, migrant, and corporate entrepreneurship in the context of the Balkans
Description based on publisher supplied metadata and other sources
Keywords: Entrepreneurship; Aufsatzsammlung